A comparative study of fetal cardiovascular assessment: utilizing Doppler ultrasound gated MRI and echocardiography with detailed analysis using five axial views - Hergert, B.; Tavares de Sousa, M.; Herrmann, J.; Bannas, P.; Huber, L.; Götz, S.; Hecher, K.; Adam, G.; Dargahpour Barough, M.; Schoennagel, B. P. (Frontiers in Cardiovascular Medicine, 2024)
Objectives To investigate the diagnostic performance of fetal cardiovascular magnetic resonance imaging (MRI) using Doppler ultrasound (DUS) gating for the evaluation of the standardized five axial views in comparison with fetal echocardiography. Methods In this prospective study 29 pregnant women (median: 34.4 weeks of gestation) underwent fetal cardiovascular MRI using DUS gating at 3 Tesla. The standardized five axial views in prenatal screening (fetal abdomen, four-chamber view, left ventricular outflow tract, right ventricular outflow tract, and three-vessel view) were independently assessed and analysed by both fetal MRI and fetal echocardiography on the same day. Image analysis included qualitative assessment and quantitative measurements of cardiovascular structures. MR image quality was assessed using a 4-point scale (from 1 = low to 4 = excellent). Postnatal echocardiography was performed for validation. Results 17/28 fetuses (60.7%) had pathological findings [16 congenital heart defect (CHD), one diaphragmatic hernia] in prenatal echocardiography. One fetus was excluded due to severe motion. Overall sensitivity and specificity in detecting fetal cardiac abnormalities was 88% and 100%, respectively, for fetal MRI and 100% and 100% for fetal echocardiography. MR image quality for evaluation of cardiac structures was high with a mean score of 2.8 (±0.8) (score 4: 15.9%, score 3: 53.8%, score 2: 19.3%, score 1: 11%). Quantitative measurements did not differ between fetal cardiovascular MRI and fetal echocardiography (all p > 0.05). Conclusion Diagnostic performance of fetal cardiovascular MRI using DUS gating was comparable to fetal echocardiography. Fetal cardiovascular MRI using DUS gating might be a valuable diagnostic adjunct for the prenatal evaluation of CHD.